Tracking the early signals of crude oil in seawater and plankton after a major oil spill in the Red Sea - Sreejith Kottuparambil; Ananya Ashok; Alan Barozzi; Grégoire Michoud; Chunzhi Cai; Daniele Daffonchio; Carlos M. Duarte; Susana Agusti (Environmental Science and Pollution Research, 2023)
Understanding the immediate impacts of oil spills is essential to recognizing their long-term consequences on the marine environment. In this study, we traced the early (within one week) signals of crude oil in seawater and plankton after a major oil spill in October 2019 in the Red Sea. At the time of sampling, the plume had moved eastward, but we detected significant signs of incorporation of oil carbon into the dissolved organic carbon pool, resulting in a 10–20% increase in the ultraviolet (UV) absorption coefficient (a 254 ) of chromophoric dissolved organic matter (CDOM), elevated oil fluorescence emissions, and depletion of the carbon isotope composition (δ 13 C) of the seawater. The abundance of the picophytoplankton Synechococcus was not affected, but the proportion of low nucleic acid (LNA) bacteria was significantly higher. Moreover, specific bacterial genera ( Alcanivorax , Salinisphaera , and Oleibacter ) were enriched in the seawater microbiome. Metagenome-assembled genomes (MAGs) suggested that such bacteria presented pathways for growing on oil hydrocarbons. Traces of polycyclic aromatic hydrocarbons (PAHs) were also detected in zooplankton tissues, revealing the rapid entry of oil pollutants into the pelagic food web. Our study emphasizes the early signs of short-lived spills as an important aspect of the prediction of long-term impacts of marine oil spills.